Leben weben: (Auto-)Biographische Praktiken russischer Autorinnen und Autoren im Internet - Howanitz, Gernot (transcript, 2020)
An innovative approach to (auto-)biographical practices on the Russian literary Internet that combines qualitative and quantitative perspectives.